Ferroelectric domains in the multiferroic phase of ErMnO3 imaged by low-temperature photoemission electron microscopy. (18th March 2015) - Schaab, J; Trassin, M; Scholl, A; Doran, A; Yan, Z; Bourret, E; Ramesh, R; Meier, D
Abstract: Low-temperature photoemission electron microscopy (PEEM) is used to image and compare the distribution of ferroelectric domains in multiferroic ErMnO3 above and below the magnetic ordering temperature ( T N = 80 K). Our temperature-dependent PEEM data demonstrate that the ferroelectric domain structure is robust against the onset of magnetic long- range order and the emergence of antiferromagnetic domains. The observed persistence indicates that antiferromagnetic domain walls adopt the position of ferroelectric walls – and not vice versa – developing a multiferroic domain-wall pattern congruent with the ferroelectric domain-wall distribution observed above T N .